GIS based approach in land suitability analysis of Lokta (Daphnee bholua) - Tripathi, S.; Adhikari, H.; Ghimire, S. (Journal of Agriculture and Forestry University, 2020)
Land suitability analysis is a pre-requisite in achieving optimum utilization of the available land resources. The main objective of this study was to develop a suitability map for lokta based on topographic, soil, land-use, land cover, and climatic factors of production using a Multi-Criteria Evaluation (MCE) & GIS approach. The study was carried out in Suspa Community Forest of Dolakha district. Biophysical variables of soil, climate, topography, and land use land cover (LULC) and water availability were considered as variable influencing for the study suitability classes. For MCE, Pairwise Comparison Matrix was applied and the suitable areas for lokta crop were generated and graduated. Finally, the land cover map was overlaid with the suitability map to identify variances between the present land cover. The crop-land evaluation results of this study showed that out of total 625 hectare area, 9% was under highly suitable, 22% were moderately suitable, 36% of the land was marginally suitable, and 33% were currently and permanently also not suitable. Also the suitable classes were overlaid over present land use and land class. It was found that 100% of the highly suitable land was under forest land of land use and hardwood of land cover. Thus findings of this research provided information at local level that could be useful in determining suitability status of desired species.